(untitled) (Nonlinear Studies, 2001)
The purpose of this paper is to develop comparison principles and study the existence and uniqueness of solutions for fuzzy differential equations under a more general condition than that of Lipschitz. Continuity of solutions as well as the global existence of the solution assuming local existence are also studied.